MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI TEKNIK KOLASE RAGAM KATA (KORAKA) DARI MEDIA KORAN PADA SISWA KELAS VIII-J SMP NEGERI 6 SURABAYA - Galuh Safitri; Erlinda Dwi Fitriana; Vina Febriana; Faridatus Zulfa; Rahma Hanifa; Qanita Azmy; Rahayu Pujiastuti; Fetty Nurindah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Eighth-grade students in Class VIII-J at Surabaya Public Junior High School No. 6 face difficulties when writing poetry because they struggle to find inspiration, choose the right words, and create vivid imagery. The class achievement rate was only 25%, with an average class score of just 61.5. Based on this, this study aims to improve the poetry-writing skills of eighth-grade students in Class VIII-J at SMP Negeri 6 Surabaya through the application of the KORAKA (Word Variety Collage) technique using newspaper media. This study is a Classroom Action Research (CAR) conducted in cycles based on the Kemmis and McTaggart model. Each cycle consists of the planning, implementation, observation, and reflection stages. The research subjects were 32 students in Class VIII-J at SMP Negeri 6 Surabaya. Data were collected through documentation, observation, tests, and questionnaires. Data analysis was conducted using both quantitative and qualitative descriptive methods. The results showed a significant improvement in each cycle. In the pre-cycle, the class average score of 61.5 increased to 70.8 in Cycle 1 and to 80.3 in Cycle 2. The rate of mastery increased from 25% to 53.1% and finally reached 84.4%, exceeding the 80% success indicator. Students’ active participation also increased from 40% to 87.5%. These results indicate that the KORAKA technique using newspapers has been proven to improve the poetry-writing skills of eighth-grade students in Class VIII-J at SMP Negeri 6 Surabaya